PJMHS 2021
DOI: 10.53350/pjmhs2115103417
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Dyslipidemia in Ischemic Stroke Patients Presented to Tertiary Care Hospital of Lahore

Abstract: Background and Aim: A stroke, also known as a cerebrovascular accident, is defined as the sudden onset of a focal neurologic deficit caused by a disruption in blood flow to parts of the brain. The purpose of this study was to evaluate the frequency of dyslipidemia in stroke patients. Materials and Methods: This cross-sectional study was carried out on 184 stroke patients in Medical department of Services Hospital, Lahore for duration of six months i.e from November 2020 to June 2021. All the stroke patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In various geographical regions and among diverse ethnic groups, the age at which women become mothers is consistently identified as the primary risk factor associated with hydatidiform mole. 22 A number of studies have proposed that molar pregnancy is strongly associated with specific factors. These factors include nulliparity (having never given birth), lower socioeconomic status, and deficiencies in essential nutrients such as protein, folic acid, and carotene.…”
Section: Resultsmentioning
confidence: 99%
“…In various geographical regions and among diverse ethnic groups, the age at which women become mothers is consistently identified as the primary risk factor associated with hydatidiform mole. 22 A number of studies have proposed that molar pregnancy is strongly associated with specific factors. These factors include nulliparity (having never given birth), lower socioeconomic status, and deficiencies in essential nutrients such as protein, folic acid, and carotene.…”
Section: Resultsmentioning
confidence: 99%
“…Also, dyslipidemia is more common in older age patients >65 years (63.2%) 28 . Consistent with these outcomes, we also found that the mean age of the patients with dyslipidemia was significantly higher than those without.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of males and females was 79% and 21%, respectively, as reported by a local study. Furthermore, they found that the prevalence of dyslipidemia in men and women was 68.4% and 43.7%, respectively 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of hyperlipidemia in patients presenting with ischemic stroke was 37.1% in another study conducted in Multan on 178 patients. 7 Hyperlipidemia is an important risk factor for occurrence of stroke; our main aim is to assess the prevalence of hyperlipidemia in tertiary care hospitals in Karachi as many studies have been done in Pakistan but mostly level of low density lipoproteins or triglyceride levels have been the main point of concern however in our study we have studied the whole lipid profile and also looked into the levels of high density lipoproteins which act as cardio protective as well as a protective agent for stroke. There is a dearth of reliable figures for the prevalence of hyperlipidemia in Pakistan.…”
Section: Introductionmentioning
confidence: 99%